2018
DOI: 10.31742/ijgpb.78.3.5
|View full text |Cite
|
Sign up to set email alerts
|

Cross transferability of finger millet and maize genomic SSR markers for genetic diversity and population structure analysis of barnyard millet

Abstract: The genomic information available in barnyard millet is very scarce though it is a rich source of highly digestible proteins and dietary fibre with good amounts of soluble and insoluble fractions. In the present investigation, 64 maize and finger millet genomic SSRs were used for cross transferability analysis among barnyard millet cultivated and wild species for identification of polymorphic markers, syntenic regions, genetic diversity and population structure analysis. Out of the 64 SSRs, only 39 (61%) were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 20 publications
0
1
0
Order By: Relevance
“…Babu and Chauhan (2017) also found homology of some barnyard millet ESTs against the chromosomal regions of 2, 5, 6, 8, 9, and 12 of rice, the waxy gene of maize, granule-bound starch synthase I (GBSSI-S) gene of Panicum repens, Setaria italica, Panicum miliaceum, and super oxide dismutase (SOD) gene of Colletotrichum eremochloae. On the other hand, Babu et al (2018a;2018b) compared rice, maize, and finger millet gSSRs for cross species amplification in barnyard millet and reported that maize and finger millet SSRs exhibited higher PIC values, efficient cross species amplification, and polymorphism percentage than rice SSRs. However, the comparative genetic mapping between rice and barnyard millet showed several putative syntenic regions across the genome that regulated the traits including seed dormancy, plant height, panicle length, spikelet characters, leaf senescence, seed weight/yield-related traits, shattering character, root traits, blast resistance, brown plant hopper (BPH) resistance, and amylose content (Babu et al, 2018b).…”
Section: Comparative Genomics and Synteny Analysesmentioning
confidence: 99%
“…Babu and Chauhan (2017) also found homology of some barnyard millet ESTs against the chromosomal regions of 2, 5, 6, 8, 9, and 12 of rice, the waxy gene of maize, granule-bound starch synthase I (GBSSI-S) gene of Panicum repens, Setaria italica, Panicum miliaceum, and super oxide dismutase (SOD) gene of Colletotrichum eremochloae. On the other hand, Babu et al (2018a;2018b) compared rice, maize, and finger millet gSSRs for cross species amplification in barnyard millet and reported that maize and finger millet SSRs exhibited higher PIC values, efficient cross species amplification, and polymorphism percentage than rice SSRs. However, the comparative genetic mapping between rice and barnyard millet showed several putative syntenic regions across the genome that regulated the traits including seed dormancy, plant height, panicle length, spikelet characters, leaf senescence, seed weight/yield-related traits, shattering character, root traits, blast resistance, brown plant hopper (BPH) resistance, and amylose content (Babu et al, 2018b).…”
Section: Comparative Genomics and Synteny Analysesmentioning
confidence: 99%